Plastic Waste Management in Rwanda : An Ex-post Policy Analysis - Xie, Jian; Martin, J. (World Bank, Washington, DC, 2022)
Rapid economic growth and poor environmental management have Rwanda facing growing pollution problems, including solid waste and plastic pollution, among others. For years, Rwanda has sought to tackle plastic waste, and the country has been proactive in pursuing environmental management with ambitious policy measures. Since 2000 when the government of Rwanda introduced its Vision 2020, the nation has progressed in introducing waste management practices that included a structured approach to sustainable waste management. Rwanda’s continued efforts include the ambitious adoption of legislative bans on the manufacture, importation, use and sale of polyethylene bags in 2008. The country recently took this effort further, with a ban on the manufacture, importation, use and sale of plastic bags and single-use plastic items. Rwandans embrace these policies through a culture where citizens work together to better their communities through collective actions or Umuganda, a practice (now enshrined in law) that requires residents to support the nation’s cleanliness. Combined, these policies have led to the near eradication of polythene bags in Rwanda and an increase in affordable waste collection services for most urban populations, especially in Kigali. The purpose of this report is to review lessons learned from an ex-post analysis of the policies regarding plastic pollution management in Rwanda and provide evidence-based recommendations for policy improvements in the country.